2016
DOI: 10.1136/heartjnl-2015-309154
|View full text |Cite
|
Sign up to set email alerts
|

Psychological stress and short-term hospitalisations or death in patients with heart failure

Abstract: Objective Standard predictors do not fully explain variations in the frequency and timing of heart failure (HF) adverse events (AEs). Psychological stress can trigger acute cardiovascular (CV) events, but it is not known whether stress can precipitate AEs in HF patients. We investigated prospective associations of psychological stress with AEs in patients with HF. Methods 144 HF patients (77% male; 57.5±11.5, range 23–87 years, LVEF≤40%) were longitudinally evaluated for psychological stress (Perceived Stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Whereas APS is known to associate with acute left ventricular dysfunction as in Takotsubo cardiomyopathy, CPS has also been shown to have adverse outcomes in established heart failure (HF) patients. Endrighi et al showed in a prospective study that CPS was a significant predictor of cardiovascular morbidity and all-cause mortality in HF patients [73]. The association between CPS and incident HF is rather weak and has largely been reported in individuals with poor health at baseline [74].…”
Section: Heart Failurementioning
confidence: 99%
“…Whereas APS is known to associate with acute left ventricular dysfunction as in Takotsubo cardiomyopathy, CPS has also been shown to have adverse outcomes in established heart failure (HF) patients. Endrighi et al showed in a prospective study that CPS was a significant predictor of cardiovascular morbidity and all-cause mortality in HF patients [73]. The association between CPS and incident HF is rather weak and has largely been reported in individuals with poor health at baseline [74].…”
Section: Heart Failurementioning
confidence: 99%
“…In the present project, we have defined these predictors as "dyad-related" because they will be measured in both patients and caregivers. The results of individual studies conducted on DM, COPD and HF patients have shown that self-care is poorer when patients and caregivers are stressed (Endrighi et al, 2016;Kaptein et al, 2009;Dionne-Odom et al, 2017), are depressed (Bourbeau & Bartlett, 2008 Vellone et al, 2017) conducted on patients (Riegel & Dickson, 2008) and caregivers . According to these two theoretical studies, self-care maintenance influences self-care monitoring and self-care monitoring influences self-care management.…”
Section: Predictors Of Self-carementioning
confidence: 99%
“…To further elucidate how recurrent cardiac events might alter the trajectory of perceived stress post-AMI (29), we performed a sensitivity analysis examining sex difference in PSS-14 scores over time among patients with versus without post-AMI angina separately. Patients with an SAQ angina frequency score less than 100 at either 1-month or 12-month interviews were regarded as having angina post-AMI, while those with a score of 100 at both interviews were considered as not having angina post-AMI.…”
Section: Methodsmentioning
confidence: 99%